The Proficiency of Islamic Religious Education and Ethics Teachers in Malang City in the Implementation of the Independent Learning Curriculum at SMPN 3 and SMPN 22 Malang City - Arifin, Syamsul; Ridwan, Muhtadi; Ali, Nur; Barizi, Ahmad (International Journal Labs, 2024)
In any situation, education remains a priority in the sustainability of human civilization as history has proven that with education all solutions to life are better obtained. Teachers in the implementation of education are one of the main factors in the implementation of quality education, so that the proficiency of a teacher must be in accordance with the competency standards that have been set. The Covid-19 that occurred in the world, including in Indonesia, provides a lesson so that everyone makes adjustments in the learning process without face-to-face or online learning (online). This study uses a descriptive qualitative approach with several focuses of this research (1) Teacher Proficiency: Analyzing the skills possessed and those that need to be improved in the implementation of the curriculum, (2) Teacher Response: Identifying how PAI and Ethics teachers respond to the implementation of the Independent Learning Curriculum (3) Government Support: Examining support from local governments to improve teacher proficiency and (4) Necessary Changes: Identify changes that need to be adopted to improve teacher proficiency. The results showed that substantially, there was no gap in teacher education qualifications in both schools. The government, both central and regional, has supported through various funds and development programs, such as workshops and training. In 2023, funds have been allocated to improve the skills of 103 PAI and BP teachers through collaboration with UIN Malang. The teacher's response to the Implementation of the Independent Learning Curriculum was very positive. They feel a fun and innovative impact, give them the freedom to design learning, and create contextual learning. It contributes to the enthusiasm of students and the development of their intellect, spirituality, and morality.